Childhood adversity, emergent psychopathology, and adolescent-to-parent violence: Process mining trajectories from police and health service administrative data - Peck, Allison; Hutchinson, Marie; Provost, Steve (Frontiers in Child and Adolescent Psychiatry, 2023)
Aim: To discover developmental risk trajectories for emerging mental health problems among a sample of adolescent family violence offenders to inform service delivery focused on early preventative interventions with children and their families. Design: A retrospective case-series design employing data linkage. Setting: An Australian regional location. Participants: Adolescents (born between1994 and 2006) issued a legal action by the NSW Police Force for an adolescent-to-parent family violence offense (n = 775). Procedure: Discrete routinely collected episode data in police and health service electronic records for children, and police data for parents, were linked and transformed into longitudinal person-based records from birth to 19 years to identify trajectories for mental health problems. Results: Sixty-three percent (n = 489) of adolescents had contact with a mental health service before age 19. The majority of these adolescents received a diagnosis for a stress or anxiety disorder (n = 200). Trajectory analysis found childhood exposure to parental intimate partner violence and parental drug and/or alcohol use were dominant events in the pathway to receiving a mental health diagnosis. Being a victim of a sexual offense was found to increase the odds of adolescents having a diagnosis for each of the main mental health categories (with the exception of drug or alcohol disorders). Conclusions: Pathways to mental health problems were characterized by inter-related adverse childhood events and poly-victimization for many adolescents. Early identification of at-risk children must be a continued focus of child health services in order to reduce and identify early emerging mental health problems.